The Impact of Teacher-Student Relationships on Students' Perceptions of Teachers' Educational Effectiveness - Agrawa, Shobhit; Sagi, Sriram; Srinivasaiah, Bharath; Ray, Narendra Kumar (Journal of Research in Vocational Education, 2024)
The impact of teacher-student relationship on student perception of the teacher's effectiveness in the delivery of education lies in the limited understanding of how the teacher-student relationship specifically shapes students' perception of the education provided by the teacher. While numerous studies have explored the impact of teacher-student relationships on various educational outcomes, such as academic achievement and student engagement, there is a lack of research specifically examining how this relationship affects students' perceptions of the teacher's educational qualifications. This study aimed to determine whether a positive and strong teacher-student relationship can influence students' perception of their teachers' knowledge and expertise in the subject matter being taught among Bachelor of Technical Vocational Teacher Education (BTVTEd) college students. This descriptive, correlational and causal-comparative quantitative study was conducted to 94 BTVTEd college students of Tagum City College of Science and Technology Foundation, Inc. using an adapted-modified survey questionnaire checklist. In addition, correlation analysis and simple linear regression analysis were used in interpreting the obtained data. Findings showed a high correlation between teacher-student relationship and students' perceptions on teacher's effectiveness in the delivery of education. Thus, teacher-student relationship factor specifically teaching style significantly influences how the BTVTEd college students perceived their teacher's effectiveness in the delivery of education.